Improvements in patient-reported outcomes after treatment with deucravacitinib in patients with psoriatic arthritis: results from a randomized phase 2 trial - Strand, V; Gossec, L; Coates, LC; Ogdie, A; Choi, J; Becker, B; Zhuo, J; Lehman, T; Nowak, M; Elegbe, A; Mease, PJ; Deodhar, A (Wiley, 2024)
Objective Deucravacitinib, a tyrosine kinase 2 inhibitor, was assessed in a phase 2 trial in patients with active psoriatic arthritis (PsA). Here, we report effects of deucravacitinib from the patient perspective.